ANALISIS DISTRIBUTION CENTER PADA PT ANUGRAH ARGON MEDICA DENGAN PENDEKATAN TATA LETAK DAN FASILITAS - Nugroho, Khristian Edi; Susanto, Edward Sutrisno (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
Warehouse design has an important role in a supply chain system, so it requires a good planning. This study aims to determine and select the warehouse location with the companys management criteria and optimal design of warehouse layout, followed by designing the layout and the existing facilities at the warehouse in accordance with the principles of the warehouse layout design. The layout design refers to: (1) facility layout problem (FLP) which is divided into Static, Dynamic and Stochastic Layout Problem, (2) facility re-layout problem (FRLP), (3) systematic layout planning (SLP). Warehouse site selection uses value of consideration factors which are keys of success of the company. After the step of location selection is location determination of the warehouse uses calculation of both extrapolation request and the required number of racks, while warehouse layout design uses the activity relationship chart, activity relationship diagram, and area allocation diagram to determine the room positions and warehouse facilities in the area. After doing the whole calculations, the location chosen for the new warehouse is at Cipondoh, Tangerang. The number of racks required is 98 retail shelves, 213 bulky shelves, 412 pallets, 69bulky and heavy duty racks. Based on the activity relationship chart (ARC), activity relationship diagram (ARD), and area allocation diagram (AAD), the warehouse layout is obtained for the new warehouse at Cipondoh that can be applied by the company for building Distribution Center project.